Human rights : concept and standards - Symonides, Janusz (Aldershot, Hants, England ; Burlington, Vt. : Ashgate ; Paris : UNESCO, 2000)
"This volume presents reflections on historical perspectives and philosophical foundations of human rights. It gives a detailed analysis of civil, political, economic, social and cultural rights as well as the rights of persons belonging to such vulnerable groups as women, children, minorities, indigenous people and migrant workers, and the interrelation between humanitarian law and human rights."--BOOK JACKET.
1. International Human Rights in an Historical Perspective / Thomas Buergenthal -- 2. The Philosophical Foundations of Human Rights / Jerome J. Shestack -- 3. Civil and Political Rights / Manfred Nowak -- 4. Economic and Social Rights / Asbjorn Eide -- 5. Cultural Rights / Janusz Symonides -- 6. Women's Rights / Katarina Tomasevski -- 7. The Rights of the Child / Yuri Kolosov -- 8. The Rights of Persons Belonging to Minorities / Hurst Hannum -- 9. Protection of the World's Indigenous Peoples and Human Rights / Erica-Irene A. Daes -- 10. Migrant Workers' Rights / Faruk Sen and Sedef Koray -- 11. Humanitarian Law and Human Rights / Hector Gros Espiell.
Includes bibliographical references and index.
Keywords: Human rights; Civil rights